Data structures for business programming - Knapp, Judith. (McGraw-Hill, 1989)
Introducing data structures. Files and their structures. Arrays, sorting, and searching. Linked lists. Stacks, Queues, and deques. Directories, inverted files, and hashing. Binary trees, multi-way trees, and B-trees.